A novel 1D van der Waals V2PSxSe10-x (x=7-10) anode for enhanced electrochemical kinetics and high-rate performance via Se alloying in lithium-ion batteries - Zhang, Xiaojie; Dong, Xue; Woo, Chaeheon; Kim, Yeongjin; Kang, Jinsu; Kim, Kyung In; Kim, Yeong Hyeop; Lee, Donghyeon; Kim, Minjae; Mun, Junyoung; Yu, Hak Ki; Choi, Jae-Young (Royal Society of Chemistry, 2025)
This study modifies the novel one-dimensional van der Waals material V2PS10 by alloying it with selenium (Se) at varying ratios, enhancing its electronic conductivity and optimizing charge distribution. These improvements reduce polarization and significantly enhance its electrochemical performance. V2PSxSe10-x (x = 5-10) series materials were synthesized, and those with x = 7-10 were measured. The results showed that the V2PSxSe10-x (x = 7-10) series achieved capacities close to theoretical values at 0.1 A g-1, and the alloyed V2PSxSe10-x (x = 7-9) exhibited excellent rate performance and long-term cycling stability under high-rate conditions. Among them, V2PS9Se retained 83% of its capacity after 400 cycles at 1 A g-1, highlighting its potential as a promising anode material for lithium-ion batteries (LIBs). Electrochemical behavior and kinetic mechanisms of pristine V2PS10 and alloyed V2PS9Se were investigated. Density functional theory (DFT) calculations comparing charge density and charge density difference revealed the effects of Se alloying on the performance of V2PS10. Additionally, phase transitions and morphological changes during the lithiation/de-lithiation processes were studied, providing new strategies and theoretical guidance for designing high-performance LIB anode materials.